POLA ASUH ORANG TUA DALAM KAJIAN KOMUNIKASI : IMPLIKASI TERHADAP HUBUNGAN KELUARGA - Rifqi Fauzi; Mia Nur Islamiah (Jurnal Bimbingan Penyuluhan Islam, 2023)
Parenting style is an important factor in building children's character and forming healthy family relationships. This research is a Literature Review or literature review. Literature research or literature review (literature review, literature research) is research that examines or critically reviews knowledge, ideas, or findings contained in academic-oriented literature, and formulates theoretical and methodological contributions for certain topics. . In this journal, we will discuss parenting styles in communication studies, by exploring the types of parenting styles, their effects on child development, as well as the implications for family relationships that explain how the relationship between parenting styles and healthy family relationships, the impact of parenting styles that are bad in family relationships and explain how strategies to improve family relationships through changes in parenting styles applied by parents.